AsnB, regulated by diffusible signal factor and global regulator Clp, is involved in aspartate metabolism, resistance to oxidative stress and virulence in Xanthomonas oryzae pv. oryzicola. (16th November 2012) - Qian, Guoliang; Liu, Chunhui; Wu, Guichun; Yin, Fangqun; Zhao, Yancun; Zhou, Yijing; Zhang, Yanbing; Song, Zhiwei; Fan, Jiaqin; Hu, Baishi; Liu, Fengquan
Summary Xanthomonas oryzae pv. oryzicola (Xoc) causes bacterial leaf streak in rice, which is a destructive disease worldwide. Xoc virulence factors are regulated by diffusible signal factor (DSF) and the global regulator Clp. In this study, we have demonstrated that asnB (XOC_3054), encoding an asparagine synthetase, is a novel virulence‐related gene regulated by both DSF and Clp in Xoc. A sequence analysis revealed that AsnB is highly conserved in Xanthomonas. An asnB mutation in Xoc dramatically impaired pathogen virulence and growth rate in host rice, but did not affect the ability to trigger the hypersensitive response in nonhost (plant) tobacco. Compared with the wild‐type strain, the asnB deletion mutant was unable to grow in basic MMX (–) medium (a minimal medium without ammonium sulphate as the nitrogen source) with or without 10 tested nitrogen sources, except asparagine. The disruption of asnB impaired pathogen resistance to oxidative stress and reduced the transcriptional expression of oxyR, katA and katG, which encode three important proteins responsible for hydrogen peroxide (H2O2) sensing and detoxification in Xanthomonas in the presence of H2O2, and nine important known Xoc virulence‐related genes in plant cell‐mimicking medium. Furthermore, the asnB mutation did not affect extracellular protease activity, extracellular polysaccharide production, motility or chemotaxis. Taken together, our results demonstrate the role of asnB in Xanthomonas for the first time.